Sistem Pakar Jenis Ulos di Acara Adat Batak Toba Menggunakan Metode Forward Chaining - Yolanda Y.P. Rumapea; Margaretha Yohanna (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
With the rapid development of technology, the type of ulos used is an obstacle in the traditional party of Batak Toba, Ulos is an object used in a traditional activity that is very important for Batak Toba people. Many types of ulos in Batak Toba therefore require a long time and ineffective results to look ulos types that are suitable for traditional activities. An expert system is a system that attempts to adopt human knowledge to computers, and one alternative to detect the type of ulos that will be used for certain customary activities. Through an expert system, it is easier to detect ulos types that are suitable for use in these customary activities, and also requires an accurate identification process to provide the right decision results. The identification method that used is forward chaining method. The usefulness of this research is to help users to access ulos types that are suitable for use in Batak Toba custom activities.